STUDI ANALISIS MODEL DAN PENDEKATAN FATWA HUKUM KELUARGA KONTEMPORER DI KALANGA ULAMA’ MODERAT - Syukur, Musthofa; Husni, Zainul Muin (JURNAL HAKAM, 2022)
Basically the authority to determine Islamic law (tasyri') rests with God and His Messenger. Apart from being explicitly stated in the Qur'an, explicit information (qath'i) is also general in nature, mujmal (dhanni). So that in the verses that are dhanni it is necessary to carry out ijtihad as an explanation of syara' demands and answers to the socio-cultural conditions and development of society. Human understanding and thinking of the second type of legal verses is called fiqh, its nature can change and is not eternal. The activities of the clergy in the process of understanding and developing Islamic law can be seen from the influence of the social and cultural conditions where the clergy are located. The contemporary fiqh that the author refers to here is contemporary Islamic law. Islamic jurists tend to interpret the meaning of contemporary Islamic law with Masa'il al-Fiqhiyah, so there is a tendency to reduce the meaning of contemporary Islamic law to the area of study of fiqh or issues that have developed in the last period. further strengthens the hypothesis about the order and relevance of fiqh-fiqh with real life contexts. Fiqh is basically not theoretical sciences (ulum al-nazariah), but its field of work is positive regulations (ahkām 'amaliyah). The contemporary family law fatwa approach uses the fiqh al-maqashid paradigm. This fiqh paradigm emphasizes the importance of attention as well as in-depth understanding of the factors or things that are the goal or reason (illat) in a legal decision, not just understanding the textual normative aspects of the provisions, fiqh al-awlawiyat. This fiqh paradigm emphasizes the selection of what is the most important of the important or between the important and the unimportant fiqh al-muwazanat.